Efficiency of the Indian Stock Market : Analysis of Semi-Strong Form of Bonus Information - Bharath, M.; Shankar, H. (Indian Journal of Research in Capital Markets, 2015)
This paper tested the semi-strong form of efficiency of the Indian stock market on the basis of information relating to bonus announcements based upon the price reaction of stocks for a period of 10 years from 2003 - 2012. Event study methodology was applied, and an event window was constructed for a period of 41 days. The AARs and CAARs were analyzed by classifying the bonus issues into small and large sizes, to ascertain whether an opportunity was available to make abnormal returns during the price adjustment period. The results evidenced that the announcements of large size bonus were better than small size bonus announcements in terms of price adjustment indicating market efficiency in the semi strong form.